2020
DOI: 10.1186/s12889-020-08813-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health education on knowledge and behavior toward respiratory infectious diseases among students in Gansu, China: a quasi-natural experiment

Abstract: Background The respiratory infectious diseases (RID) threaten the health and life quality of school students. However, previous related studies were insufficient in research design and method applied. This study aimed to evaluate the effect of health education on the knowledge and behavior of students toward RID through difference-in-difference (DID) analysis in Gansu, China. Methods In 2015–2016, a one-year health education program in Gansu, China was conducted. The intervention group contained 1064 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
2
15
0
6
Order By: Relevance
“…Since mastitis can be found through physical examination, clinical intervention for patients with mastitis found in the physical examination is the key to improving symptoms and enhancing the quality of life [ 4 , 5 ]. In addition to the necessary drug treatment, scientific rehabilitation exercise and health education are also effective measures to improve the outcomes of mastitis [ 6 ]. Health education is conducive to deepening patients' understanding of their own diseases, enhancing their self-care ability, improving treatment compliance, and establishing healthy living habits, which has been confirmed in diseases such as vitiligo, adolescent idiopathic scoliosis, and osteoporotic vertebral compression fractures [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since mastitis can be found through physical examination, clinical intervention for patients with mastitis found in the physical examination is the key to improving symptoms and enhancing the quality of life [ 4 , 5 ]. In addition to the necessary drug treatment, scientific rehabilitation exercise and health education are also effective measures to improve the outcomes of mastitis [ 6 ]. Health education is conducive to deepening patients' understanding of their own diseases, enhancing their self-care ability, improving treatment compliance, and establishing healthy living habits, which has been confirmed in diseases such as vitiligo, adolescent idiopathic scoliosis, and osteoporotic vertebral compression fractures [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study health education (healthy snacks, healthy nutrition (including label reading) importance of physical activity) to address such issues as increasing obesity rates in school-age children, children's malnutrition, and inadequate exercise. The study findings demonstrated that health education positively affected students' health behaviors (Wang & Fang, 2020). Another experimental study that aimed to improve eye health in primary school-age children reported that eye health-protective behaviors increased positively (Kirag & Temel, 2018).…”
Section: Knowledgementioning
confidence: 84%
“…The setting of these studies varied from the household setting (n = 4) (14, 16, 23, 27), over the hospital and healthcare facilities (n = 7) (7,9,10,(24)(25)(26)28), schools (n = 6) (15,17,18,(29)(30)(31), and University setting (n = 2) (20,22), to the corporation worksites (n = 2) (8, 21) and one study was performed on Hajj pilgrims (19).…”
Section: Resultsmentioning
confidence: 99%
“…The outcome assessment was different between articles. Although the educational interventions were highly variable and often multimodal, all but three studies ( 8 , 14 , 15 ) addressed and emphasized that educational interventions are successful in influenza prevention in terms of respiratory tract infection incidence ( 16 22 ), vaccination rate ( 7 , 9 , 23 25 ), and improvement of knowledge or preventive behaviors ( 9 , 26 30 ) ( Tables 1 – 3 ).…”
Section: Resultsmentioning
confidence: 99%